Condition Monitoring of Lubricant in Static Mechanisms Using Pulse-Echo Ultrasound Technique - Ali M.; Simic M.; Imad F.; Nagi F. (Elsevier B.V., 2023)
Fuzzy inference; Knowledge based systems; Lubricants; Signal processing; Ultrasonic applications; Ultrasonic testing; Ultrasonics; Wavelet transforms; Classification system; Fuzzy inference systems; Mechanical components; Pulse echo ultrasound; Pulse-echo technique; Ultrasonic inspection system; Ultrasonic testing method; wavelet; Condition monitoring